2021
DOI: 10.1093/aob/mcab074
|View full text |Cite
|
Sign up to set email alerts
|

Increased seminal root number associated with domestication improves nitrogen and phosphorus acquisition in maize seedlings

Abstract: Background and Aims Domesticated maize (Zea mays ssp. mays) generally forms between two and six seminal roots, while its wild ancestor, Mexican annual teosinte (Zea mays ssp. parviglumis), typically lacks seminal roots. Maize also produces larger seeds than teosinte, and it generally has higher growth rates as a seedling. Maize was originally domesticated in the tropical soils of southern Mexico, but it was later brought to the Mexican highlands before spreading to other parts of the continen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 99 publications
1
29
0
Order By: Relevance
“…Increased lateral root production leads to more soil exploration and helps in improving phosphorus capture. This also aligns with findings that increased numbers of seminal roots in domesticated maize improved nutrient capture (Perkins & Lynch, 2021).…”
Section: Environmental Regulation Of Root Development and Growth: Dro...supporting
confidence: 89%
See 1 more Smart Citation
“…Increased lateral root production leads to more soil exploration and helps in improving phosphorus capture. This also aligns with findings that increased numbers of seminal roots in domesticated maize improved nutrient capture (Perkins & Lynch, 2021).…”
Section: Environmental Regulation Of Root Development and Growth: Dro...supporting
confidence: 89%
“…Seminal root numbers have increased in domesticated grasses such as maize and barley compared to their wild relatives, which may improve nutrient acquisition. It was shown that seminal roots contributed to approximately 35% of total phosphorus and nitrogen uptake in the first 25 days of seedling growth in maize landraces (Perkins & Lynch, 2021). The physiological basis for the senescence of the embryonic root system has not been well investigated and may result as a consequence of a regulated developmental program or from being starved of resources due to the rapid growth of the postembryonic root system.…”
Section: Overview Of Root Types In Grass Root Systemsmentioning
confidence: 99%
“…Maximum ear weight (115.8 g) was noticed when 120 kg P ha -1 was applied while minimum (109.4 g) was observed when 90 kg P ha -1 was applied. Ear weight of maize crop increased with higher rate of phosphorus because phosphorus increases the amount of endosperm in grain (Perkins et al, 2021). Similar in case of Zn, maximum ear weight (129.6 g) was noticed when 5 kg Zn ha -1 was applied while minimum (113.4 g) was noticed with water spray only.…”
Section: Resultsmentioning
confidence: 66%
“…One strategy was to develop a deep SR system with an optimal number of branches, such that the benefit of having more branches outweighs the effect of competition, enabling early vigorous root growth with deep soil exploration. SR are known to be important for seedling vigor during early development (Hochholdinger et al., 2018, Perkins & Lynch, 2021). In wheat, by the time the NR appear, the SR system was found to be up to 40 cm deep in the soil.…”
Section: Discussionmentioning
confidence: 99%